Studi Analisis Dampak Overload Transformator Terhadap Kualitas Daya Di PT. PLN(Persero) Up3 Pondok Gede - Samsurizal Samsurizal; Benyamin Hadinoto (Sekolah Tinggi Teknik - PLN, 2020)
The population of the population in big cities, special areas of the big cottage growth continues to increase according to the BPS in 2015 amounted to 2,733,240 and increased in 2019 3,013,851. With an increasing population, it will increase electricity demand in the region. The JS 190 Distribution Station provided a significant increase in transformer loading which achieved a 95.75% loading presentation of a 200 kVA transformer capacity. Therefore it is necessary to improve by looking at these conditions, one of which is by doing an uprating transformer or adding a power transformer with a larger capacity to 400 kVA. From the results of the increase obtained loading results decreased to 52.75% which means the reversal transformer is one method that can be used to overcome the overload.